1980
DOI: 10.1111/j.1365-2230.1980.tb01709.x
|View full text |Cite
|
Sign up to set email alerts
|

Incisional procedures and prognosis in malignant melanoma

Abstract: A total of seventy-six patients with cutaneous malignant melanoma were analysed with relation to the prognostic influence of incisional biopsies. Of these, sixty-two underwent primary radical surgery, whereas fourteen patients had an incisional procedure prior to definitive treatment. Multivariate analysis revealed that survival was markedly reduced after incisional procedures. Other important prognostic factors were ulceration, age and sex. We believe that punch or incisional biopsies taken to substantiate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…Ironside et al found a five-year OS rate of 66% in the excision- and 43% in the incision biopsy group but failed to describe the distribution of prognostic factors between both groups 10. Rampen et al also found a worse prognosis for patients after an incision biopsy (14 patients) but the study was small and retrospective 11. Griffiths et al found no difference in survival but 7/19 incisional biopsy patients were excluded because of missing histopathological data 12.…”
Section: Discussionmentioning
confidence: 99%
“…Ironside et al found a five-year OS rate of 66% in the excision- and 43% in the incision biopsy group but failed to describe the distribution of prognostic factors between both groups 10. Rampen et al also found a worse prognosis for patients after an incision biopsy (14 patients) but the study was small and retrospective 11. Griffiths et al found no difference in survival but 7/19 incisional biopsy patients were excluded because of missing histopathological data 12.…”
Section: Discussionmentioning
confidence: 99%
“…However, a pathologic examination of a biopsy of the lesion is required for a definitive diagnosis and determination of the tumor thickness. The influence of the type of biopsy on the patient outcome in melanoma, specifically, whether an incisional biopsy causes local or systemic tumor dissemination, has been debated [5,6,7,89]. Rampen et al [5] reported a decreased survival rate in a group of 14 patients who had incisional biopsies compared with that of 62 patients who had excisional biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the type of biopsy on the patient outcome in melanoma, specifically, whether an incisional biopsy causes local or systemic tumor dissemination, has been debated [5,6,7,89]. Rampen et al [5] reported a decreased survival rate in a group of 14 patients who had incisional biopsies compared with that of 62 patients who had excisional biopsies. In a study on head and neck melanomas, Austin et al [6] reported a decreased survival rate among patients who had incisional, shave, or needle aspiration biopsies compared with those who had excisional biopsies, although a significant age difference was noted among the patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Concern over local, regional, or systemic metastasis was prompted by prior studies and case reports which suggested a poor outcome for patients undergoing subtotal biopsy techniques. 87,[101][102][103][104][105][106][107][108][109][110][111][112] When comparing 14 patients who underwent incisional biopsy with 62 patients who had an excision for diagnosis in a retrospective study, Rampen, van Houten, and Jop 110 in 1980 were able to demonstrate reduced survival with incisional biopsy. However, they did not stratify for other factors related to survivability between the two groups.…”
Section: Margins and Metastasismentioning
confidence: 99%